Short-term evolution of Po della Pila delta lobe from time lapse high-resolution multibeam bathymetry (2013–2016). (5th February 2020) - Bosman, Alessandro; Romagnoli, Claudia; Madricardo, Fantina; Correggiari, Annamaria; Remia, Alessandro; Zubalich, Riccardo; Fogarin, Stefano; Kruss, Aleksandra; Trincardi, Fabio
Abstract: Over the last few years (2013–2016) repeated high-resolution multibeam surveys were carried out at the recent-most delta lobe of the Po river (in correspondence to Po della Pila). The collected multibeam bathymetry together with backscatter data, seabed samples and high-resolution seismic profiles provided insights on the short-term morphological and sedimentological evolution of this extremely dynamic submarine portion of the delta. A high variety of geomorphological features and depositional bodies were observed from the mouth bar to the prodelta slope such as, for example, the alongshore and transverse bars (formed under the effect of marine currents), gravitational-instability phenomena and collapse depressions (driven by fluid expulsion). Concurrently, the analysis of the seabed reflectivity and sediment samples allowed the identification of two main dominant types of seafloor sediment, corresponding to sandy and muddy seabed and the mapping of their variable distribution in the study area. The comparison of time-lapsed, high-resolution DEMs showed that the main changes occurred on the northern side of the prodelta slope, where a new lobe-shaped fine-sediment deposit built up to 4.5 m adding roughly a volume of 1.16 Mm 3 of new sediments. At the same time in the prodelta slope transverse depositional bars showed a clear migration toward the south of the system and local subsidence phenomena up to 1.5 m between 7 and 10 m water depth are observed. Highlights: Subsidence in the Po River Delta. Submarine landslides in the Po River Delta. Bedforms and sediment transport processes.